COMBINATION OF STRETCHING WITH IMMERSION SYSTEM (COLD AND CONTRAST) ON DOMS PAIN TOLERANCE - Sartika, Dewi (Sport and Fitness Journal; Vol 9 No 2 (2021): Volume 9, No. 2, May 2021, 2021)
Introduction: DOMS is a complaint of muscle pain experienced by athletes by exercising overloadedly. DOMS pain tolerance improvement was carried out with several interventions, in the form of a combination of stretching with cold water immersion, and stretching with contrast water immersion. The purpose of this research is to proving which comparison of physiotherapy interventions is better for DOMS pain tolerance improvement. Method: The research was carried out in the Ngurah Rai athletics field in Denpasar in January 2020, experimental in nature with a pretest and post test two group design. Samples were male athletes divided into two groups, each group consisting of 9 respondens. Group I was given a combination of stretching and cold water immersion, Group II was given a combination of stretching and water immersion in contrast. Cold water temperature is 10 ?C and warm water temperature 36-40 ?C. Pain tolerance value measured by sphygmomanometer placed on the calf. The higher the value mmHg, the higher the tolerance would be. Result: Results in Group I, the mean pain tolerance before intervention was 153 ± 7.76 (mmHg) and the mean after intervention (48 hours) 206 ± 8.32 (mmHg) with p = 0,000 (p <0.05). In Group II, the mean pain tolerance before intervention was 154 ± 8.35 (mmHg) and after intervention (48 hours) 188.4 ± 6.95 (mmHg) with a value of p = 0,000 (p <0.05). This showed a significant increase in pain tolerance in each group. Statistical tests conducted between the two groups also showed significant differences, with a result of p = 0,000 (p <0.05) where the value of pain tolerance in Group I was better than Group II. Conclusions: combination of stretching and cold water immersion is better than the combination of stretching and water immersion in contrast in reducing DOMS.     Keywords: Delayed onset muscle soreness ; stretching ; cold water ; contrast water immersion .